The Energy Potential of Waste from Banana Production: A Case Study of the Mediterranean Region - Atilgan Atilgan; Anna Krakowiak-Bal; Hasan Ertop; Burak Saltuk; Mateusz Malinowski (Energies, 2023)
Recently, with the development of technology, the number of studies on the need for energy and the possibilities of covering this need in a sustainable way has been increasing. The management of agricultural biomass and waste is cited as one of the challenges as well as a solution. Mersin and Antalya sites, where banana production is intensively practiced in Turkey, were selected as the study region. The potential amounts of energy values obtained from the waste generated during banana cultivation in the field area of study were calculated. The energy potential was calculated on the basis of the conversion of biogas that can be obtained from the waste. The values obtained were analyzed and compared with the levels of electricity used to determine the economic gains that can be achieved for Mersin and Antalya regions. The data on bananas used in study were obtained from the Turkish Statistical Institute (for the years 2016–2020). It is calculated that 2884.43 MWh of electricity can be generated in Mersin and 2218.26 MWh in Antalya per 5 years from the waste generated during banana production. The values of the number of houses whose needs can be met with the calculated five-year potential electricity amount are 1237 in Mersin and 952 in Antalya. It can be considered that reusing the potential energy that can be obtained from banana waste, examined as material for energy, used in agricultural production will result in a positive impetus to agricultural activities. Energy obtained from banana waste can cover a very small amount of the electrical energy needs of agricultural production, ranging from 0.19% to 0.34%. However, it is concluded that the potential amount of energy to be obtained by recycling not only banana waste but also other agricultural and food waste will be even higher.